2009
DOI: 10.1111/j.1553-2712.2009.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

The Business of Emergency Medicine: A Nonclinical Curriculum Proposal for Emergency Medicine Residency Programs

Abstract: Over the course of their postgraduate medical education, physicians are expected not only to acquire an extensive knowledge of clinical medicine and sound procedural skills, but also to develop competence in their other professional roles as communicator, collaborator, mediator, manager, teacher, and patient advocate. Although the need for physicians to develop stronger service delivery skills is well recognized, residency programs may underemphasize formal training in nonclinical proficiencies. As a result, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…In the changing U.S. health care environment, physicians are required to perform a wider variety of tasks and have a deeper understanding of nonmedical topics, such as health policy and healthcare economics. Studies have shown a lack of familiarity with principles in health policy and practice management among residents and recent graduates across a number of medical specialties [1][2][3][4][5], prompting numerous proposals and calls to action to improve health policy education within graduate medical education [6][7][8][9][10][11]. Although studies have characterized business preparedness among dermatology trainees [12,13], efforts to understand and educate dermatology trainees about health policy reforms pertaining to dermatology practice have not been required or standardized across dermatology residency programs [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In the changing U.S. health care environment, physicians are required to perform a wider variety of tasks and have a deeper understanding of nonmedical topics, such as health policy and healthcare economics. Studies have shown a lack of familiarity with principles in health policy and practice management among residents and recent graduates across a number of medical specialties [1][2][3][4][5], prompting numerous proposals and calls to action to improve health policy education within graduate medical education [6][7][8][9][10][11]. Although studies have characterized business preparedness among dermatology trainees [12,13], efforts to understand and educate dermatology trainees about health policy reforms pertaining to dermatology practice have not been required or standardized across dermatology residency programs [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional postgraduate physician education focuses on learning the clinical aspects of a physician’s career. There is a lack of published literature on how training programs address needs such as leadership education and career development [ 1 - 5 ]. A 2017 study of anesthesia residency programs revealed that only 23 of 59 programs had a career development curriculum (CDC) and of those CDCs available, 32.2% were rated as poor or completely ineffective by their program directors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 A few medical and surgical specialties have attempted to address this issue by incorporating single or limited courses on topics such as leadership or general management. [5][6][7][8] Although there is some evidence that a web-based curriculum improves the business knowledge of residents, 9 to date, a proper needs assessment -what specifically such a curriculum should look like and how to best deliver it -has not been completed.…”
mentioning
confidence: 99%